Academic satisfaction with teaching in the virtual modality during the COVID-19 pandemic as perceived by nursing students - Maylle Sayes, Belgica (2024)
Objective. To evaluate academic satisfaction with the virtual modality implemented during the COVID-19 pandemic, as perceived by students of the Nursing Program at the Universidad de Huánuco (Peru) in 2021. The study aimed to identify areas of satisfaction and aspects for improvement, particularly in technological accessibility and the quality of support services. Methods. This was a quantitative study with a simple descriptive, cross-sectional design. The population consisted of 713 students, with a probabilistic sample of 250. A validated academic satisfaction scale and an online survey technique were used for data collection, followed by descriptive statistical analysis. Results. A total of 89.2% of students reported satisfaction with the virtual modality. Among the dimensions evaluated, technological acceptance achieved 86.1% satisfaction, and personal achievements reached 87.6%. Additionally, 70.9% positively evaluated university support services. However, 10.8% of students expressed dissatisfaction, primarily due to connectivity issues and the quality of certain support services, which negatively impacted their academic experience. Conclusion. Most students perceived high satisfaction with virtual learning, highlighting the accessibility and usefulness of technological tools. Areas of dissatisfaction underscore the need to improve connectivity and some support services, which are essential to optimizing virtual education in the university context.